2017
DOI: 10.1111/jam.13577
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of fungal communities of developmental stages in table grape grown in the northern region of South Africa

Abstract: The information on fungal diversity and succession in table grapes during preharvest growth stages is critical in the development of a more targeted control strategy, to improve postharvest quality of table grapes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 42 publications
(87 reference statements)
3
13
0
Order By: Relevance
“…This is significant because during pea size growth stage, pathogen proliferation is compromised (Harshman et al, 2014;Jia et al, 2016), further confirming the sensitivity of the ddPCR, as shown in previous work (Dreo et al, 2014). It is also important to note that pyrosequencing analysis of the same samples used in our present study did not detect B. cinerea (Carmichael et al, 2017), showing that ddPCR was more sensitive in this regard.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This is significant because during pea size growth stage, pathogen proliferation is compromised (Harshman et al, 2014;Jia et al, 2016), further confirming the sensitivity of the ddPCR, as shown in previous work (Dreo et al, 2014). It is also important to note that pyrosequencing analysis of the same samples used in our present study did not detect B. cinerea (Carmichael et al, 2017), showing that ddPCR was more sensitive in this regard.…”
Section: Discussionsupporting
confidence: 89%
“…Our results revealed a higher concentration of B. cinerea on samples collected from vines located towards the centre of the vineyard than those on the periphery. A conducive microclimate within the vineyard and exposure to sunlight providing a 'sterilizing' effect on peripheral grape bunches have been recently reported to promote and limit pathogen proliferation (Carmichael et al, 2017), respectively. This is a view supported by results of our current report because microclimate manipulation can directly or indirectly affect pathogen growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yeast biodiversity was low (Table ), as reported in previous studies where increasing ethanol during winemaking reduces the yeast biodiversity of wine, limiting it to a few species of yeast (Ribéreau‐Gayon et al ; Barata et al ). Pleosporales , highly represented in grape, have already been found among dominant fungi on grapes before harvesting (Carmichael et al ). Seimatosporium spp.…”
Section: Discussionmentioning
confidence: 97%
“…Although they are mainly used as table grapes for consumption, many local growers also use them for wine fermentation, obtaining better value from wines, especially when table grapes are in excess supply and the price drops substantially. Although some work has been done on the table grape microbiome, most researchers have focused on the surface of the berry during the mature stage, and concentrated on the control of postharvest diseases (Kántor & Kačániová, 2015;Carmichael et al, 2017). Little has been done to study yeast species involved in table grape fermentations.…”
Section: Introductionmentioning
confidence: 99%